Pelatihan Dakwah Digital Pimpinan Cabang Aisyiyah Purwokerto Timur sebagai Upaya Optimalisasi Dakwah Perempuan Berkemajuan di Era 4.0. : Digital Da'wah Training For Aisyiyah Purwokerto Timur Branch Leaders as An Effort to Optimize Progressive Women's Da'wah in The 4.0 Era - Mildaeni, Itsna Nurrahma; Hasanah, Uswatun; Muharudin, Eko (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2025)
Aisyiyah, as a progressive Islamic women's movement affiliated with Muhammadiyah, has long contributed to promoting women's roles through da'wah in education, health, and socio-economic sectors. In the era of digital transformation, the ability to leverage digital media for da'wah becomes increasingly crucial. However, many regional branches, such as PCA (Pimpinan Cabang Aisyiyah) Purwokerto Timur, still rely heavily on conventional methods, facing challenges in effectively utilizing digital tools. This community service initiative by Universitas Muhammadiyah Purwokerto aimed to empower PCA cadres through digital da'wah training that combines conceptual learning and hands-on practice using Canva. The training consisted of three core sessions: (1) understanding the concept of progressive Islamic women's da'wah, (2) strategies for creative digital da'wah, and (3) technical skills in designing da'wah materials. Statistical analysis using the Wilcoxon Signed-Rank Test indicated a significant improvement in participants' knowledge and skills, with the average post-test score (M = 37.32) significantly higher than the pre-test score (M = 31.72, p < 0.05). Participants also showed increased confidence and competence in producing visually engaging and meaningful content for online da'wah. This program highlights the significance of capacity building for grassroots Islamic organizations to remain relevant and impactful in the digital era.